Social Study Learning Model At Primary School - Fitria Dwi Prasetyaningtyas; Wasino Wasino; Cahyo Budi Utomo; Arif Purnomo (International Conference on Science, Education, and Technology, 2023)
A community refers to groups of individuals living in a place and interacting with one another. Individual interaction causes various cultural diversity and must be anticipated to manage social problem emergences. Social science is important to instill an understanding of cultural variety. Thus, diversity preservation will last excellently and construct the global citizen attitude. Therefore, an accommodative learning model is important to improve the attitude and social values of primary school learners. The learning model refers to the described learning from the beginning until the end of a lesson specifically made by the teachers. A learning model is the mode or framework of an approach, a method, a strategy, or a learning technique. The learning model has some syntactic components as the primary reference of all phases to apply the concepts of the learning model. This literature review attempted to determine the applied learning model for social science learning at primary schools.